OBESITY: CHALLENGES TO VENTILATORY CONTROL DURING EXERCISE A BRIEF REVIEW - Babb, Tony G. (2013)
Obesity is a national health issue in the US. Among the many physiological changes induced by obesity, it also presents a unique challenge to ventilatory control during exercise due to increased metabolic demand of moving larger limbs, increased work of breathing due to extra weight on the chest wall, and changes in breathing mechanics. These challenges to ventilatory control in obesity can be inconspicuous or overt among obese adults but for the most part adaptation of ventilatory control during exercise in obesity appears remarkably unnoticed in the majority of obese people. In this brief review, the changes to ventilatory control required for maintaining normal ventilation during exercise will be examined, especially the interaction between respiratory neural drive and ventilation. Also, gaps in our current knowledge will be discussed.